2009
DOI: 10.1897/08-651.1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stressor effects of methoprene, permethrin, and salinity on limb regeneration and molting in the mud fiddler crab (UCA pugnax)

Abstract: Exposure to multiple stressors from natural and anthropogenic sources poses risk to sensitive crustacean growth and developmental processes. Applications of synthetic pyrethroids and insect growth regulators near shallow coastal waters may result in harmful mixture effects depending on the salinity regime. The potential for nonadditive effects of a permethrin (0.01 2 gg/L), methoprene (0.03-10 tg/L ), and salinity (10-40 ppt) exposure on male and female Uca pugnax limb regeneration and molting processes was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Research with the freshwater amphipod, Hyalella azteca, indicated similar results with growth inhibition at levels as low as 44-73 ng g −1 (Amweg et al, 2005;Holmes et al, 2008). Results from Stueckle et al (2009) suggested that permethrin disturbed limb regeneration and moulting in the mud fiddler crab, Uca pugnax. Singh and Srivastava (1999) found a significant reduction in the activity of lactate dehydrogenase and cytochrome oxidase and an enhancement in succinate dehydrogenase activity in the tissues of the freshwater fish, Channa striatus, exposed to permethrin.…”
mentioning
confidence: 82%
“…Research with the freshwater amphipod, Hyalella azteca, indicated similar results with growth inhibition at levels as low as 44-73 ng g −1 (Amweg et al, 2005;Holmes et al, 2008). Results from Stueckle et al (2009) suggested that permethrin disturbed limb regeneration and moulting in the mud fiddler crab, Uca pugnax. Singh and Srivastava (1999) found a significant reduction in the activity of lactate dehydrogenase and cytochrome oxidase and an enhancement in succinate dehydrogenase activity in the tissues of the freshwater fish, Channa striatus, exposed to permethrin.…”
mentioning
confidence: 82%
“…Similarly, those invertebrates that undergo specialized growth and re-generation may also be especially susceptible to the effects of sublethal pyrethroid exposure. For instance, chronic exposures to permethrin (<2 µg/L) disrupted male fiddler crab (Uca pugnax) limb re-generation, although female limb development was unaffected (Stueckle et al, 2009). …”
Section: Impacts On Aquatic Invertebrate Growthmentioning
confidence: 99%
“…For example, Van der Geest et al () showed strong interaction between hypoxia and Cu toxicity in the mayfly Ephoron virgo : whereas 50% reduction in O 2 content and Cu concentration of 50 μg/L separately had no effect on the survival of the mayflies, the 2 factors combined resulted in 50% mortality. In marine ecosystems, the synergetic effect of increased salinity on the toxicity of chemicals has been demonstrated (Stueckle et al ; Lavado et al ). In terrestrial ecosystems, exposure to toxicants has been shown to significantly decrease drought tolerance.…”
Section: Most Potent Natural Factors In Combination With Toxicantsmentioning
confidence: 99%